Denial-of-service resistance in key establishment. (30th May 2007) - Smith, Jason; Tritilanunt, Suratose; Boyd, Colin; Gonzalez Nieto, Juan M.; , Ernest Foo
Denial of Service (DoS) attacks are an increasing problem for network connected systems. Key establishment protocols are applications that are particularly vulnerable to DoS attack as they are typically required to perform computationally expensive cryptographic operations in order to authenticate the protocol initiator and to generate the cryptographic keying material that will subsequently be used to secure the communications between initiator and responder. The goal of DoS resistance in key establishment protocols is to ensure that attackers cannot prevent a legitimate initiator and responder deriving cryptographic keys without expending resources beyond a responder-determined threshold. In this work we review the strategies and techniques used to improve resistance to DoS attacks. Three key establishment protocols implementing DoS resistance techniques are critically reviewed and the impact of misapplication of the techniques on DoS resistance is discussed. Recommendations on effectively applying resistance techniques to key establishment protocols are made.